Peran Strategi Diferensiasi dalam Meningkatkan Jumlah Wisatawan (Studi Kasus Kampung Coklat Blitar) - Andriani; Toriqotus Sa’adah (Sharia Business Management Study Program, Faculty of Economics and Islamic Business at IAIN Kediri, 2021)
Differentiation is an attempt by a company to differentiate its products from competitors’ products in a trait that makes them more desirable. The differentiation strategy includes product differentiation strategy, service differentiation, personal differentiation, differentiation channel, and image. The kampung Coklat educational tour was established on 17 August 2014 and has successfully implemented a differentiation strategy in increasing the number of tourism with the objectives of the study are (1) Knowing the differentiation strategy in educational tourism in Kampung Coklat Blitar: (2) Knowing the role of the differentiation strategy in increasing the number of tourists in kampung Coklat Blitar. This study uses a qualitative approach, where the presence of researchers in the field is needed. Data collection methods in this study are observation, interviews, and documentation. Checking the validity of the data by means of triangulation. The data analysis used was data reduction, data presentation, and conclusion drawing. The results of the research are 1) Kampung Coklat Blitar carrying out its tourism object business using a differentiation strategy consisting of five dimensions, namely product, service, personnel, channel, and image dimensions. Kampung Coklat also strives to optimize all its differentiation dimensions to increase attractiveness. By continuing to develop tourist attractions as creatively as possible, build, complete facilities for the comfort and satisfaction of visitors. 2). The implementation of the differentiation strategy carried out by Kampung Coklat has played a very big role in increasing the number of tourists from 2017 to 2019, experiencing an increase in the number of visitors by 13.68%.